A case for 'anticipatory leadership' : Christian eschatology and anticipation as a leadership competency for ministers in 'an age of perplexity' - Vrey, Daniel Divan (Stellenbosch : Stellenbosch University, 2022)
Thesis (MTh)--Stellenbosch University, 2022.